Answer:
![ln((8)/(5x) )=ln(8)-ln(5)-ln(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/p9q5oswyxmw0qkc1vm56t35yq6hzzs6rcc.png)
Explanation:
Use the properties of logarithms on each step:
First use the property for the logarithm of a quotient:
![ln((a)/(b) )=ln(a)-ln(b)](https://img.qammunity.org/2021/formulas/mathematics/high-school/108s6tfvjrr336t98gzg5lwgbanm9hy7eq.png)
So we get:
![ln((8)/(5x) )=ln(8)-ln(5x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/vlekmxr1ti8dervgaj5kcb20xef4mxtgxy.png)
Now, we can expand the last term using the property of logarithm of a product:
![ln(a\,*\,b)=ln(a)+ln(b)](https://img.qammunity.org/2021/formulas/mathematics/high-school/h49dwf69qnxona3p0erb69zwrydsod9dax.png)
Therefore we write
![ln(5x)=ln(5)+ln(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/kd4tbwd5pfd6c4s0hnz1a61la1tci6xedo.png)
No we insert this result in the subtraction we had before:
![ln((8)/(5x) )=ln(8)-ln(5x)=ln(8)-(ln(5)+ln(x))=ln(8)-ln(5)-ln(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/gh8id94m04zq5z96wwiljqize77imgyly6.png)